Strategi Kesantunan Positif Tokoh-Tokoh dalam Novel 7 Prajurit Bapak Karya Wulan Nuramalia - Putri Wahyuni; Ngusman Abdul Manaf (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2023)
This study aims to explain the substrategy of positive politeness used by the characters in Wulan Nuramalia's 7 Soldiers, and how the context of the speech situation uses each of these speech strategies in Wulan Nuramalia's 7 Soldiers. This type of research is qualitative research using descriptive methods. The data of this research are in the form of utterances contained in the dialogues of the characters in the novel 7 Soldier Bapak. The source of the research data is in the form of speech acts that use speech strategies with positive politeness performed by the characters in the novel 7 Soldiers of the Father by Wulan Nurmalia. The data collection technique used is the observation and note taking technique. In this study the data validation technique used in this study was the triangulation technique. Based on the data collected and analysis of research data, the results of this study are as follows. (1) Found 14 types of positive politeness substrategy used by the characters in the novel 7 Soldiers Bapak by Wulan Nurmala from 132 speech data with the following details. Substrategies involve participants in activities, use markers of group intimacy, joke around, give and ask reasons, offer help and promises, pay more attention/give recognition/sympathy, focus on speech partners, use agreements, give gifts, be optimistic, intensify attention , and the three substrategi that were found the least were assuming and displaying the similarity of actions, avoiding conflicts, and equating assumptions into general opinion. (2) The context of the speech situation using each positive politeness substrategy in the novel 7 Soldier Bapak found 6 contexts, namely (a) The context of the speaker's speech situation has greater power (+K) and is not yet familiar (-S), (b) The context of the speaker's speech has greater power (+K) and already familiar (+S), (c) The speaker's context is lower in power (-K) and not yet familiar (-S), (d) The speaker's context is lower in power (-K) and already familiar (+S) ), (e) The context of the speaker has the same power as the speaker (=K) and is not yet familiar (-S), (f) The context of the speaker has the same power as the speaker (=K) and is already familiar (+S).